A Critical Examination on the Lorentz Contraction of a Rod - Hermanto, Arief; Hanang Setya Budhi, Romy (Universitas Negeri Semarang, 2024)
When studying special relativity, we usually find Lorentz contraction as one of the most clear andstraightforward consequences of the Lorentz Transformation. The derivation of Lorentz contractionfrom Lorentz Transformation is apparently so simple that we usually overlook an important idealassumption. A body which is Lorentz contracted is assumed to exist in infinite time in its rest frameof reference. In this paper we will derive Lorentz contraction without that assumption. We willderive Lorentz contraction (using spacetime diagram) of a rod with finite lifetime in its rest frame ofreference. The result is such that the famous Lorentz contraction formula is only valid in certaincondition concerning the lifetime of the rod.